Produção de mucina e expressão de HIF-1a e VEGF-A em modelo de câncer colorretal induzido em ratos suplementados com farinha de yacon (Smallanthus sonchifolius) - Tamiasso, Natalia Viana (2017)
Yacon (Smallanthus sonchifolius) is a functional food due to its capacity to promote health benefits, but its effect on colorectal cancer is still unknown. Thus, the objective was to evaluate intestinal mucin production and identify hypoxia-inducible factor1alpha (HIF-1a) and vascular endothelial growth factor A (VEGF-A) expression in experimental rat model of induced colorectal cancer supplemented with yacon. Forty three Wistar rats were allocated into four experimental groups: C: untreated group; N: 1,2-dimethylhydrazine-treated (DMH-treated) group; Y: yacon-treated group; NY: DMH + yacon-treated group. The induction of neoplastic cells followed a protocol of one infection with DMH per week during five weeks. After induction and neoplastic development period, the diets supplemented with yacon flour were given during eight weeks. Intestinal samples were stained with hematoxylin-eosin, periodic acid-Schiff (PAS) and Alcian Blue (AB) and went under immunohistochemistry protocols with anti-HIF-1a and anti-VEGF-A antibodies. The lesions found were lymphocytosis, lymphoid hyperplasia, glandular dilation, atypical epithelium, dysplasia, adenomas and adenocarcinomas. Animals from group N have had reduction in neutral mucin production and there was no difference in acid mucin production among the groups. Animals from NY group showed decrease in HIF-1a expression while Y and NY groups had VEGF-A expression, similar to the control group. In conclusion, alimentary supplementation with yacon flour increases neutral mucin production in animals with induced colorectal cancer but do not alter acid mucin production. Besides, yacon consumption decreases HIF-1a expression, and did not interfer in VEGF-A expression.